(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
After Independence, the managers of the Indian economyfound that the world has been sharply divided into two blocks: the one led bythe capitalist economies and other led by the communist economies, primarilythe then USSR. There was a cold war between these two blocs. Less developedeconomies had no option than to join either of the two and invite the ire ofthe opposite bloc. Especially those economies that were under the BritishEmpire and won freedom during 1940’s faced a difficult choice. India chose tokeep a safe distance from both the blocks by inventing the idea of a mixedeconomy. In doing so, India invited as much favor as suspicion from both theblocks. Some economists hold the opinion that the Indian economy waspro-capitalism in its core that wore the façade of a socialistic economy. Thestate-managed economic endeavors facilitated capital formation in the privatesector, often at the cost of the public sector and resources, preparing for asmooth transition to open capitalism in future when the conditions were ripefor such a transition.